HIDROLISIS MINYAK KELAPA DENGAN LIPASE TERIMOBILISASI ZEOLIT PADA PEMBUATAN PERISA ALAMI - moentamaria, dwina; Agaian, Girlian; Ridhawati, Meilita Mustika; Chumaidi, Achmad; Hendrawati, Nanik (Jurnal Bahan Alam Terbarukan, 2016)
Free Fatty acid  resulting from hydrolisis of  various types of oil enzymatically has been great interest recently to save energy, in other hand  that the product are environmentally friendly.  Lipases as biocatalysts for synthesis reactions  will  be  dissolved with the product, making difficult their reuse. Efficiency can be done with the use of enzyme immobilization, which can be used for repeated reaction. The products of free fatty acids from coconut oil by hydrolysis of lipase can be used as a natural substrate for making flavor  that can be consumed and safe for health. The effect of free lipase and  immobilization of lipase on hydrolisis  were studied.   Reaction time of hydrolisis was varied as 30, 60, 90, 120 and 150 minutes. The  variation  of concentration of lipase  addition was 4, 5, 6, 7 and 8 % .  The types of treatment were used in this research free lipase and the immobilized lipase. The results shows that the highest conversion on hydrolisis of coconut oil  by using free lipase treatment  was performed by 6 % of lipase addition  with reaction time 60 minutes that are 52,31%. While, the highest conversion on hydrolisis of coconut oil by using the immobilized lipase was shown  by 8% of lipase addition with reaction time 120 minutes that is 56,01%.  The results of the hydrolysis process in the form of fatty acid was used as the base material esterification process resulting ester product (natural flavor). Ester yield was produced by free lipase esterification was 28,21 and 32,14 % in immobilized  lipase  esterification.